Experimental Observation of Bright and Dark Solitons Mode-Locked with Zirconia-Based Erbium-Doped Fiber Laser. (February 2018) - Markom, A. M.; Tan, S. J.; Haris, H.; Paul, M. C.; Dhar, A.; Das, S.; Harun, S. W.
Abstract : We demonstrate the generation of dark and bright solitons with our homemade zirconia-based erbium-doped fiber and graphene oxide (GO) saturable absorber in anomalous dispersion region. The GO is fabricated using an abridged Hummer's method, which is combined with polyethylene oxide to produce a composite film. The film is sandwiched between two optical ferrules and embedded in the laser cavity to enhance its birefringence and nonlinearity. The self-starting bright soliton is easily generated at pump power of 78mW with the whole length cavity of 14.7 m. The laser produces the bright pulse train with repetition rate, pulse width, pulse energy and central wavelength being 13.9 MHz, 0.6 ps, 2.74 pJ and 1577.46 nm, respectively. Then, by adding the 10m of single mode fiber into the laser cavity, dark soliton pulse is produced. For the formation of dark pulse train, the measured repetition rate, pulse width, pulse energy and central wavelength are 8.3 MHz, 20 ns and 4.98 pJ and 1596.82 nm, respectively. Both pulses operate in the anomalous region